2021
DOI: 10.1021/acs.jpcc.1c07177
|View full text |Cite
|
Sign up to set email alerts
|

Hot-Hole-Induced Molecular Scissoring: A Case Study of Plasmon-Driven Decarboxylation of Aromatic Carboxylates

Abstract: Optically excited plasmonic nanostructures may function as molecular scissors with unique capabilities to cleave specific chemical bonds in molecular adsorbates through either plasmon-enhanced intramolecular electronic excitations or injection of photoexcited hot electrons into adsorbate orbitals. Here we chose plasmon-driven decarboxylation of aromatic carboxylates as a model reaction system to demonstrate that plasmonic hot holes, instead of electrons, could also be effectively harnessed to trigger regiosele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 79 publications
1
24
0
Order By: Relevance
“…These measurements were repeated at different random positions across each respective sample to determine an average SERS decay. It should be noted that for the experimental conditions used here no evidence of MBA decarboxylation , or other competing processes was observed in any of the measured Raman series.…”
mentioning
confidence: 99%
“…These measurements were repeated at different random positions across each respective sample to determine an average SERS decay. It should be noted that for the experimental conditions used here no evidence of MBA decarboxylation , or other competing processes was observed in any of the measured Raman series.…”
mentioning
confidence: 99%
“…Time-dependent SERS spectra of functionalized AuNPs (Figure S5) during plasmon-driven decarboxylation are displayed in Figure A,B. In contrast to that observed for catalytic experiments over AgNPs, the SERS spectrum of 2-MBA changes as the laser exposure time increases, and the appearance and steady growth of two new Raman peaks at 999 and 1072 cm –1 , assigned to the plasmon-driven production of TP, , is observed in the first seconds of the reaction (Figure C). The removal of carboxylate groups exhibited similar laser-power- and wavelength-dependence in comparison to the TP formation over AgNPs and indicated that the photocatalytic process on AuNPs is plasmon-driven as well (Figures S6 and S7).…”
Section: Resultsmentioning
confidence: 90%
“…While SERS spectra of 2-MBA did not exhibit any noticeable changes upon laser illumination (Figure C), time series SERS spectra of 4-MBA adsorbed on AgNPs show that the intensity of the COO – stretching mode of vibration at 1430 cm –1 diminishes, accompanied by the rise of new Raman peaks at 999 and 1020 cm –1 (Figure D). Additionally, the intensity of the Raman peak at 1585 cm –1 , assigned to a ring mode of 4-MBA, also decreases over time, together with the appearance of a shoulder peak at 1572 cm –1 . , These new Raman peaks are assigned to spectral features of TP (Figure D, top panel) and indicate that 4-MBA molecules adsorbed to AgNPs undergo decarboxylation to produce TP through plasmon-driven photocatalysis. , …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Briey, the uronic acid loses the carboxylic acid (carbon dioxide) group (-COOH) and the three molecules of water are removed, resulting in the formation of the corresponding furan compound under conditions of strong acidity and high temperature. 45,46 The three acid-derived components of the uronic acids, namely, 2-furan aldehyde (furfural), 5-formyl-2-furanformic acid, and reductive acid (2,3-dihydroxy-2-cyclopentene-1-one) are essentially endproducts in the reaction. 22,47 Surprisingly, during the reaction, the C-2 of uronic acid forms furfural, and the aldehyde carbon is completely from the aldehyde group of the parent uronic acid.…”
Section: Decarboxylation Reaction Of D-gal-amentioning
confidence: 99%